Evidence-Based Practice Meets Improvement Science - Slavin, Robert E. (Éducation et didactique, 2017)
Anthony Bryk is one of the most thoughtful and articulate theorists of education improvement anywhere. In his 2014 AERA Distinguished Lecture, published in the Educational Researcher (Bryk, 2015), he lays out his critique of current strategies for improving schools at scale. His purpose is to propose a “third paradigm” for school improvement. The first, often called standards-based reform, consists of the use of standards, assessments, and central reg...